Revisiting Human Rights in Islamic Thought: Normative Principles and Their Implementation in Contemporary Contexts - Edy Juarminson; Zawil Huda; Rusydi. AM; Sri Wahyuni (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: Human Rights is a fundamental issue in the global discourse that is closely related to respect for human dignity. In the Islamic tradition, the concept of human rights is not a new idea, but has been rooted theologically and philosophically in the teachings of the Qur'an and Sunnah. This research aims to analyze the concept of human rights in Islam, examine its epistemological differences with secular human rights paradigms, and evaluate its relevance and application in the context of contemporary society characterized by democracy, pluralism, and the demand for socio-economic justice. Theoretical framework: The theoretical framework of this research rests on the principles of monotheism, justice ('adl), and amanah as the foundation of Islamic human rights ethics, which is analyzed through the approach of maqāṣid al-syarī'ah as a contextual interpretive instrument. Literature review: A literature review shows that Islamic human rights studies have tended to be normative-textual or limited to comparison with Western human rights, thus emphasizing less emphasis on the applicative and transformational dimensions in modern life. Methods: This study uses a qualitative method with a literature study approach, by analyzing Islamic normative sources, contemporary Islamic thought, and modern human rights discourse critically and thematically. The data were analyzed descriptively and analytically to find conceptual patterns and the practical relevance of Islamic human rights. Results: The results of the study show that human rights in Islam are theocentric, placing Allah as the source of legitimacy of rights, while at the same time emphasizing the balance between human rights and obligations. Implications: The application of Islamic human rights in contemporary society requires the reinterpretation of religious texts based on maqāṣid al-syarī'ah to be in line with the values of justice, religious freedom, gender equality, socio-economic rights, and environmental protection. Novelty: this research lies in the affirmation of Islamic human rights as an adaptive and comprehensive ethical-religious framework, not just an alternative to Western human rights. The implications of this research are theoretical and practical, namely, strengthening Islam's position in the global human rights discourse and providing a normative foundation for the development of public policies, education, and social practices oriented towards contextually respecting human dignity.